(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The performance of banks can be measured by providing quality service to the customers in order to achieve competitive edge. The level of customer satisfaction can be determined through the quality of product or services provided to the customers and it is believed that satisfied customers develop and maintain relationship with the organization and purchase more products or services regularly than the dissatisfied customers. The purpose of this paper is to examine the impact of various service quality variables on the level of customer satisfaction and compare the private and public sector banks using a sample from Delhi NCR. The sample is consisting of responses from 240 customers of public sector banks and 238 customers of private sector banks. Forward stepwise regression was used for the purpose of analysis. The results indicated that in case of private sector banks, well managed policies for transactions security, employees’ courtesy with the customers, personalized services to customers, bank’s commitment towards the customers, have positive impact on customer satisfaction. On the other hand, in case of public sector banks, commitment towards the customers, accuracy of account information, and information about the new and attractive schemes and suggestion for the best possible course of action have positive impact on customer satisfaction.